Enhanced Salt Tolerance of Torreya grandis Genders Is Related to Nitric Oxide Level and Antioxidant Capacity - Liu, Yang; Jiang, Zhuoke; Ye, Yuting; Wang, Donghui; Jin, Songheng (Frontiers in Plant Science, 2022)
Nitric oxide (NO), a bioactive molecule, is often involved in the regulation of physiological and biochemical processes in stressed plants. However, the effects of NO donors on dioecious plants remain unclear. Using a pot experiment, female and male Torreya grandis were used to study the role of sex and NO in salt stress tolerance. In the present study, female and male T. grandis seedlings pretreated with an NO donor (sodium nitroprusside, SNP) were exposed to salt stress, and then leaf relative water content (RWC), photosynthetic pigments, chlorophyll fluorescence parameters, NO and glutathione levels, oxidative damage, and antioxidant enzyme activities were investigated. Female T. grandis plants had better tolerance to salinity, as they were characterized by significantly higher RWC, pigment content, and photochemical activities of photosystem Ⅱ (PSII) and fewer negative effects associated with higher nitrate reductase (NR) activity and NO content. Pretreatment with an NO donor further increased the endogenous NO content and NR activity of both female and male T. grandis plants compared with salt treatment. Moreover, pretreatment with an NO donor alleviated salt-induced oxidative damage of T. grandis, especially in male plants, as indicated by reduced lipid peroxidation, through an enhanced antioxidant system, including proline and glutathione accumulation, and increased antioxidant enzyme activities. However, the ameliorating effect of the NO donor was not effective in the presence of the NO scavenger (Nω-nitro-L-arginine methyl ester, L-name). In conclusion, enhanced salt tolerance in T. grandis plants is related to nitric oxide levels and the supply of NO donors is an interesting strategy for alleviating the negative effect of salt on T. grandis. Our data provide new evidence to contribute to the current understanding of NO-induced salt stress tolerance.